MAKNA SIMBOLIK DAN KULTURAL TRADISI LEBARAN KETUPAT BAGI MASYARAKAT JAWA - Sriyana, Sriyana; Suprapti, Wiwik (FISIPOL Universitas PGRI Palangka Raya, 2024)
The Ketupat Eid tradition is one of the cultural heritages of the Javanese people which is still preserved today. Eid Ketupat (kupatan) has deep value and meaning in several aspects, namely in the religious aspect as a means of spreading Islamic religion, strengthening ties of friendship, as an expression of gratitude to Allah SWT for the success of fasting during the month of Ramadan. In the spiritual aspect there is interaction to forgive each other, then in the social aspect it is a form of mutual cooperation, while in the economic aspect it can increase people's income by selling coconut leaves or palm leaves.Apart from having social meaning and value, the kupatan tradition also has symbolic meaning, namely Eid as a symbol of the end and end of the fasting month of Ramadan, luberan as a symbol of an invitation to share one's fortune by giving zakat and alms, melting as a symbol of admitting mistakes and forgiving each other, and laburan as a symbol so that humans always maintain their physical and spiritual purity. Apart from containing symbolic meaning, the Eid Kupatan tradition also contains cultural meaning, namely a means of communication and friendship, a means of giving alms, a means of honoring guests and a means of preserving ancestral traditions.